Estimating organic carbon in the soils of Europe for policy support - Jones, Robert J. A.; Hiederer, Roland; Rusco, E.; Montanarella, Luca (Blackwell Publishing, 2005)
The estimation of soil carbon content is of pressing concern for soil protection and in mitigation strategies for global warming. This paper describes the methodology developed and the results obtained in a study aimed at estimating organic carbon contents (%) in topsoils across Europe. The information presented in map form provides policy-makers with estimates of current topsoil organic carbon contents for developing strategies for soil protection at regional level. Such baseline data are also of importance in global change modelling and may be used to estimate regional differences in soil organic carbon (SOC) stocks and projected changes therein, as required for example under the Kyoto Protocol to the United Nations Framework Convention on Climate Change, after having taken into account regional differences in bulk density.